Translation of a spinal bone cement product from bench to bedside - Fei Feng (KeAi Communications Co., Ltd., 2022)
Spinal acrylic bone cements (ABCs) are used clinically for percutaneous vertebroplasty (PVP) and kyphoplasty (PKP) to treat osteoporotic vertebral compression fractures. Product translation of spinal ABC products followed the design control processes including design verification and validation. The bench to bedside translation of the first Chinese spinal ABC product (Alliment®, namely Alliment Cement) approved by National Medical Products Administration of China was investigated and another commercial product served as the control (Osteopal®V, namely Osteopal V Cement). Results of non-clinical bench performance verification tests of compression, bending and monomer release showed that the newly marketed Alliment Cement is similar to the Osteopal V Cement with properties of both meeting the criteria specified by standards. The Alliment Cement demonstrated good biocompatibility during the 26 weeks’ bone implantation test. Porcine cadaver validation tests further revealed that the Alliment Cement satisfied the needs for both PVP and PKP procedures. A post-approval, retrospective clinical investigation further demonstrated the safety and efficacy of the Alliment Cement, with a significant reduction of pain and the improved stability of the fractured vertebral bodies. A successful translation of biomaterial medical products needs close collaborations among academia, industry, healthcare professionals and regulatory agencies.